2021
DOI: 10.1038/s41598-021-83287-w
|View full text |Cite
|
Sign up to set email alerts
|

MTBP phosphorylation controls DNA replication origin firing

Abstract: Faithful genome duplication requires regulation of origin firing to determine loci, timing and efficiency of replisome generation. Established kinase targets for eukaryotic origin firing regulation are the Mcm2-7 helicase, Sld3/Treslin/TICRR and Sld2/RecQL4. We report that metazoan Sld7, MTBP (Mdm2 binding protein), is targeted by at least three kinase pathways. MTBP was phosphorylated at CDK consensus sites by cell cycle cyclin-dependent kinases (CDK) and Cdk8/19-cyclin C. Phospho-mimetic MTBP CDK site mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 82 publications
(83 reference statements)
2
19
0
Order By: Relevance
“…Inhibiting ATR/ATM alone had a smaller effect on MTBP dephosphorylation whereas Chk1 inhibition alone had no visible effect on MTBP phosphorylation ( Supplementary Figure S7 ). This observation could be explained by a cooperative effect of the checkpoint kinases as concluded in a recent study, published while our work was in revision ( 55 ). In yeast, the Treslin homologue Sld3 shifts in a DDK dependent manner in G1 phase ( 56 ).…”
Section: Resultssupporting
confidence: 70%
“…Inhibiting ATR/ATM alone had a smaller effect on MTBP dephosphorylation whereas Chk1 inhibition alone had no visible effect on MTBP phosphorylation ( Supplementary Figure S7 ). This observation could be explained by a cooperative effect of the checkpoint kinases as concluded in a recent study, published while our work was in revision ( 55 ). In yeast, the Treslin homologue Sld3 shifts in a DDK dependent manner in G1 phase ( 56 ).…”
Section: Resultssupporting
confidence: 70%
“…Quantification of replicates (Fig. 2C) confirmed these observations and proved reproducibility of our BrdU quantification method (Boos et al 2013, Ferreira et al 2021, Kohler et al 2019. Treslin/TICRR-DSTD clone 21 rescued replication somewhat better (50 % replication) than clones 11 and 17 (approximately 30 % replication; 2PM and no-transgene controls about 30%), exemplifying our observation that individual clones expressing the same transgene showed some variability that probably arise through clonal selection.…”
Section: Resultssupporting
confidence: 78%
“…In contrast, the requirement of the Sld3-homologous STD for replication had not previously been addressed in higher eukaryotes. To test this, we used incorporation of the nucleotide analogue BrdU into nascent DNA of cultured human cells in an established RNAireplacement system (Boos et al, 2011(Boos et al, , 2013 (Boos et al, 2013;K öhler et al, 2019;Ferreira et al, 2021) confirmed these observations. Treslin/TICRR-ΔSTD clone 21 rescued replication somewhat better (50% replication) than clones 11 (~30% (Boos et al, 2011;Kumagai et al, 2011), Chk1 binds to the very C-terminal 99 amino acids of Treslin (Guo et al, 2015), and Brd2/4 binds to the Treslin/TICRR region 1560-1580 (Sansam et al, 2018).…”
Section: Resultsmentioning
confidence: 93%